The cultivation of Panax notoginseng enhances the metabolites and microbial network complexity in the soil of Pinus armandii rather than Pinus kesiya - Hei, Jingying; Li, Yue; Rui, Rui; Faisal, Noor; Peng, Jiansong; Wang, Biao; Wang, Shu; He, Xiahong (Frontiers in Microbiology, 2025)
IntroductionThe species of tree most appropriate for the cultivation of Sanqi in an understory environment is pine. Nevertheless, the precise type of pine that confers the greatest benefit to soil health during Sanqi cultivation has not been definitively established.MethodsHerein, four distinct land use configurations were established, including the Pinus armandii, Pinus kesiya, Sanqi–Pinus armandii (SPA), and Sanqi–Pinus kesiya (SPK) systems. High-throughput sequencing technology and metabolomics analysis were used to comparatively evaluate variations in bacterial and fungal community structures and soil metabolites between the SPA and SPK systems.Results and discussionAfter cultivating Sanqi, the content of total phosphorus, ammonium nitrogen, and total potassium as well as water content and soil pH were significantly increased in P. armandii soil. Moreover, the bacterial and fungal copy numbers, alpha- and beta-diversity, remained unchanged in the soil of P. armandii, but significantly decreased in the soil of P. kesiya following Sanqi planting. Moreover, Sanqi cultivation significant increased complexity of the microbial network in P. armandii rather than P. kesiya soil, while the network stability was maintained. Structural equation modeling indicated that soil enzymes, metabolites, and edaphic factors enhanced the complexity of the microbial network in P. armandii soil in SPA system. Additionally, the content of eight differentially accumulated metabolites (DAMs) was significantly increased in the rhizosphere and bulk soils of P. armandii. In conclusion, the cultivation of Sanqi benefits the microbiome and metabolites in P. armandii rather than P. kesiya soil, thus providing an important theoretical foundation for the sustainable development of Sanqi cultivation.